Inovasi Teknologi Proses untuk Peningkatan Kapasitas dan Kualitas Produk pada UMKM Omah Mente Kota Malang - Nonok Supartini; Kgs Ahmadi; Sumarno Sumarno; Henny Leondro (Universitas Tribhuwana Tunggadewi Malang, 2026)
The partner of this community service activity is Omah Mente which processes chasew nut fried and chasew nut cookies. The problem faced by the partner in chasew nut fried was the variation in the quality of the final product, while in the processing of chasew nut cookies the mixing of the dough is uneven because it is still done manually. The community service program aims to improve the variation in the quality of chasew nut fried and improve the mixing process of raw materials to be more even and increase production. The solution to this problems is through process technology innovation with the introduction of a deep fryer in the processing of chasew nut fried and a planetary mixer in the processing of chasew nut cookies. The results of this community service program are the quality of chasew nut fried uniform and an increase in production of 214%. Meanwhile, the chasew nut cookies produced good quality products because they were evenly mixed and there was a 200% increase in production.ABSTRAKMitra kegiatan pengabdian kepada masyarakat ini adalah Omah Mente yang mengolah mente mente goreng dan cookies mente. Permasalahan yang dihadapi mitra pada mente goreng variasi kualitas produk akhir sementara pada pengolahan cookies mente pencampuran adonan yang tidak merata karena masih dilakukan secara manual. Program pengabdian kepada masyarakat bertujuan untuk memperbaiki variasi kualitas mente goreng dan perbaikan proses pencampuran bahan baku agar lebih merata dan peningkatan produksi. Solusi dari permasalahan tersebut dilakukan inovasi teknologi proses dengan introduksi deep fryer pada pengolahan mente goreng dan mixer planetary pada pengolahan cookies mente. Hasil program pengabdian kepada maasyarakat ini kualitas mente goreng seragam dan peningkatan produksi sebesar 214%. Sementara pada cookies mente dihasilkan produk yang kualitas baik karena merata dan terjadi peningkatan produksi sebesar 200%.